Synthesis of carbon nano-onions and their application in photovoltaic cells - Mongwe, Thomas Hlamalani (My University, 2018)
In this study the synthesis and use of multi-layered and quasi-spherical carbon nano-onions (CNOs) for use as a catalyst in dye-sensitized solar cells (DSSCs) is reported. The synthesis of CNOs was achieved following procedures reported in the literature. Two synthesis methods are reported this study; the catalytic chemical vapour deposition (CCVD) and the flame pyrolysis method (FP). To selectively synthesize CNOs using CCVD, a supported iron catalyst was prepared for the decomposition of acetylene (C2H2), used as carbon source. Sodium chloride was used as a support due to its water solubility advantage. During the CCVD synthesis at 450 °C, mixtures of carbonaceous nanomaterials were observed that included carbon nanofibres. To counter act this problem, the FP method was used and CNOs of high purity were obtained from this method. The FP method is a catalyst free method and in this study clarified butter (Ghee) was used as the carbon source as well as the fuel. The flame produced the soot material (CNOs) effectively. The carbon nanostructured materials produced from both methods were analyzed and characterized using various analytical techniques such as Branauer-Emmett-Teller (BET) analysis, Fourier Transform Infrared (FTIR) spectroscopy, Raman spectroscopy, Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), Thermo-Gravimetric Analysis (TGA), Ultra-Violet visible (UV-vis) spectroscopy, and Powder X-ray diffraction (XRD). These techniques revealed that both methods produce CNOs. However, the ones produced from the CCVD method incorporated the metal catalyst and also included carbon nanofibers (CNFs). The CNOs produced were quasi-spherical nanostructured materials with diameters less than 100 nm. Materials produced through FP, were very pure and were synthesized in good yield in gram scaled. The highly pure CNOs from the FP method were successfully doped with nitrogen (post-doped) using gaseous ammonia. Both the doped and undoped CNOs were tested in DSSCs. It was observed that both types of materials are capable of acting as a catalyst for this type of photovoltaic cells. However, the nitrogen doped material had better catalytic behavior compared to the undoped CNOs. This was attributed to the fact that doping CNOs with nitrogen promoted n-type behavior such that electron transportation in the cell was easily promoted.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfillment for the degree of Master of Science in Chemistry. Johannesburg. April 2018.